2018
DOI: 10.1080/21691401.2018.1499663
|View full text |Cite
|
Sign up to set email alerts
|

Biogenic synthesis of silver nanoparticles using extracts of Leptolyngbya JSC-1 that induce apoptosis in HeLa cell line and exterminate pathogenic bacteria

Abstract: Utilizing novel approaches for the green synthesis of metal nanoparticles are of great importance. Therefore, we reported biogenic synthesis of silver nanoparticles (AgNPs) using extracts of Leptolyngbya strain JSC-1, and their significant applications against pathogenic bacteria and cancerous HeLa cell line. The biofabricated AgNPs were characterized by UV-visible spectroscopy, FTIR, SEM, TEM, DLS and zeta-potential. The as prepared AgNPs were assessed for inhibition of bacterial growth and induction of apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 44 publications
4
13
0
Order By: Relevance
“…e moderate particles' sizes observed were 5, 12, 25, 35, and 50 nm, for AgNPs synthesized by different biological extracts using water as a solvent. Similar results were also found by other researchers recently [16,[25][26][27][28]. In an article comparing the advantages and drawbacks of these methods and the applications of nanoparticles in various domains, a synthesis of chemical, physical, and biological methods for obtaining AgNPs of different shapes and dimensions (from 2 to 300 nm) was described [29].…”
Section: Zeta Potential Analysissupporting
confidence: 77%
See 1 more Smart Citation
“…e moderate particles' sizes observed were 5, 12, 25, 35, and 50 nm, for AgNPs synthesized by different biological extracts using water as a solvent. Similar results were also found by other researchers recently [16,[25][26][27][28]. In an article comparing the advantages and drawbacks of these methods and the applications of nanoparticles in various domains, a synthesis of chemical, physical, and biological methods for obtaining AgNPs of different shapes and dimensions (from 2 to 300 nm) was described [29].…”
Section: Zeta Potential Analysissupporting
confidence: 77%
“…Low zeta potential values of particles suggest no flocculation and no tendency to assemble due to repulsion forces among particles [23,24]. e SEM images of AgNPs reported by other researchers from different extracts showed spherical particles, aggregated spherical particles, irregularly shaped particles, and cubic particles [16,25]. e moderate particles' sizes observed were 5, 12, 25, 35, and 50 nm, for AgNPs synthesized by different biological extracts using water as a solvent.…”
Section: Zeta Potential Analysismentioning
confidence: 84%
“…Biomolecules of the yeast extract play a decisive part in the formation of Ag NPs by protecting them from aggregation. Stabilizers of biomolecules help to prevent redundant reactions between Ag NPs [38]. The amphoteric molecules of amino acids contain both basic and acidic groups.…”
Section: Cytotoxicity Of Ag Nps and Analysis Of Biomoleculesmentioning
confidence: 99%
“…JSC-1 fabricated Ag-NPs extracellularly from silver nitrate after 20 min. 94,95 A recent study showed that the dispersivity and stability of silver-NPs synthesized using Oscillatoria limnetica changed with increasing time. After 48 h of synthesis, the UV spectrum wavelength value was constant, and after 9 months of incubation, the optical intensity had shifted from 0.71 to 0.599 nm, indicating about the stability of Ag-NPs with low agglomeration.…”
Section: Time Of Exposurementioning
confidence: 99%
“…37-2-1 31.86 Elongated +, - Light, dark 25 7 72 h Antibacterial agent 55 Lyngbya majuscule CUH/Al/MW-150 20–50 Spherical + Dark RT 4 72 h Antileukemic, antibacterial agent 121 Lyngby asp. +,- Dark RT NM 24 h 68 Leptolyngbya valderianum 2–20 Spherical + Dark RT 3.86 72 h Antibacterial agent 152 Leptolyngbya JSC-1 5–50 Spherical - NM RT NM 20 min Anticancer, antibacterial agent 94 Lyngbya NCCU-102 54 Spherical - Light 30 NM 24 h NM 56 Microchaete NCCU-342 40 …”
Section: Cyanobacteria As Biomachinery For Nps Synthesismentioning
confidence: 99%